Moving beyond the dilemma: practices that contribute to the on-farm management of agrobiodiversity - Boef, W.S. de; Thijssen, Marja H.; Shrestha, P.; Subedi, A.; Feyissa, R.; Gezu, G.; Canci, A.; Justiniano Da Fonseca Ferreira, Dias, T.; Swain, S.; Sthapit, B.R. (Informa UK Limited, 2012)
The definition provided by the Convention on Biological Diversity for in situ conservation has caused a dilemma for those involved in agrobiodiversity conservation, as to how to implement this strategy in practical terms. A diversity of organizations has been engaged in efforts referred to as on-farm management of agrobiodiversity. Their efforts are assessed according to their impact on socioeconomic, cultural, genetic, and ecological dynamics. This assessment enables them to move beyond the dilemma and contributes to the social construction of the methodology for community biodiversity management, which is increasingly recognized as a process for achieving in situ conservation.